2015
DOI: 10.1016/j.energy.2015.05.114
|View full text |Cite
|
Sign up to set email alerts
|

Market and policy risk under different renewable electricity support schemes

Abstract: a b s t r a c tWorldwide, renewable electricity projects are granted production support to ensure competitiveness. Depending on the design of these support schemes, the cash inflows to investment projects will be more or less exposed to fluctuations in electricity and/or subsidy prices. Furthermore, as renewable electricity technologies mature, there is a possibility that the current support scheme will be terminated or revised in ways that make it less generous or more in line with market mechanism.Using a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 28 publications
1
97
0
Order By: Relevance
“…We find that the likely provision of a subsidy lowers the relative value of the two strategies, yet stepwise investment still dominates a lumpy investment strategy even when the size of the subsidy increases. Additionally, in line with Boomsma and Linnerud (2014), we show how a retractable subsidy may facilitate investment relative to the case where the subsidy is available permanently, yet lowers the optimal capacity of a project. Moreover, we find that the sudden provision of a permanent subsidy may delay investment relative to the case in which the subsidy is never available, yet raises the amount of installed capacity.…”
Section: Related Workmentioning
confidence: 67%
See 1 more Smart Citation
“…We find that the likely provision of a subsidy lowers the relative value of the two strategies, yet stepwise investment still dominates a lumpy investment strategy even when the size of the subsidy increases. Additionally, in line with Boomsma and Linnerud (2014), we show how a retractable subsidy may facilitate investment relative to the case where the subsidy is available permanently, yet lowers the optimal capacity of a project. Moreover, we find that the sudden provision of a permanent subsidy may delay investment relative to the case in which the subsidy is never available, yet raises the amount of installed capacity.…”
Section: Related Workmentioning
confidence: 67%
“…Their results indicate that while investors with a portfolio of licences act in line with real options theory, i.e., policy uncertainty delays investment rates, investors with a single license act in line with the traditional NPV approach. Boomsma and Linnerud (2014) analyse how investment incentives are affected by the likely termination or revision of a support scheme allowing for electricity and subsidy prices to follow correlated geometric Brownian motions. Their results indicate that, expectations that a support scheme may be terminated, delay investment if it is applied retroactively, but may facilitate investment otherwise.…”
Section: Related Workmentioning
confidence: 99%
“…Applying a real options investment model, Boomsma and Linnerud (2015) argue that investment incentives do not differ strongly between green certificates and feed-in tariffs and additional risk premia under green certificates are small. Schmalensee (2012) argues that social costs under feed-in tariffs are higher due to the unknown installation quantities.…”
Section: Investments Into Renewable Energymentioning
confidence: 99%
“…Pyrgou et al [7] examined the regulatory and policy framework of FIT scheme, specifically its effect on both the electricity pricing as well as the local and European renewable energy sources market, and accordingly the definition of its feasibility as a scheme for the further development and promotion of renewable energy technologies. Boomsma et al [1] studied the market and policy risk under different renewable electricity support schemes, and they found that the differences in market risk between support schemes like FIT and RPS are less than commonly believed due to price diversification. Schallenberg-Rodriguez [8] assessed the performance of RPS system and FIT system, and analyzed their advantages and disadvantages, thereby contributing to the worldwide debate on the suitability of the different renewable energy sources support systems.…”
Section: Introductionmentioning
confidence: 99%
“…They have made institutional choices according to their energy policy goals and actual national conditions [1]. The policies and regulations of various countries are varied.…”
Section: Introductionmentioning
confidence: 99%